THE EXISTENCE OF AMERICAN RAP MUSIC AND INDONESIAN HIP HOP AS POPULAR CULTURE: A REVIEW OF AMERICAN STUDIES - Didik Murwantono (Universitas Stikubank (UNISBANK) Semarang, 2011)
This study is intended to reveal the effects of American popular culture in our home, mainly Rap music and Hip Hop music by American studies along with synthesis of knowledge. This article also highlights on how to study artifact of popular culture well, to understand more about culture, to establish a clear concept of what contextual, connotation and deep meaning of lyrics in the songs, and to get better understanding of the strong as a whole as responses toward the existence of American cultural imperialism and American hegemony in Indonesia. Globalization of media is also discussed to know how the information technology advancement of the media influences the norms and values of the society. The media has become a struggle tool in demanding a change and improvement, as well as a tool for a series of interest. Key words: Music, popular culture, global media, cultural artifact, and American Studies